Visual Estimation of Force Applied During Simulated Deliveries Complicated by Shoulder Dystocia - Margaret Walters; Allison Eubanks; Elizabeth Weissbrod; John Fischer; Barton Staat; Shad Deering (American Journal of Perinatology Reports, 2018)
Abstract